A Strategi Kepala Sekolah dalam Implementasi Perbup 37 Tahun 2022 Kab. Ponorogo Tentang Kegiatan Keagamaan: Strategi Kepala Sekolah, Implementasi Perbup, Kegiatan Keagamaan - Pradana, Adi; Junaidi, Achmad; Ahmadi, Ahmadi (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2023)
The duties and obligations of the school principal include ensuring that religious activities in schools are carried out effectively. Religious activities are an important part of education because they can help students develop a thorough understanding of religious beliefs and strengthen their religious identity. Data collection techniques include observation, interviews, and documentation. The research subjects were school principals, vice principals for curriculum and student affairs, and teaching staff. Data is analysed by condensing it (data condensation), presenting it (data display), and drawing conclusions or verifying them (conclusion drawing and verification). The results of the study show that the principal's strategy in implementing Perbup No. 37 of 2022 concerning religious activities includes: 1) cooperating with partnerships from around educational institutions; 2) providing socialisation to committees and student guardians about the importance of religious activities; and 3) publishing or giving awards to students who have graduated tahfidz.